Therapeutic and protective efficacy of a dengue antibody against Zika infection in rhesus monkeys. (June 2018) - Abbink, Peter; Larocca, Rafael; Dejnirattisai, Wanwisa; Peterson, Rebecca; Nkolola, Joseph; Borducchi, Erica; Supasa, Piyada; Mongkolsapaya, Juthathip; Screaton, Gavin; Barouch, Dan
Abstract Strategies to treat Zika virus (ZIKV) infection in dengue virus (DENV)-endemic areas are urgently needed. Here we show that a DENV-specific antibody against the E-dimer epitope (EDE) potently cross-neutralizes ZIKV and provides robust therapeutic efficacy as well as prophylactic efficacy against ZIKV in rhesus monkeys. Viral escape was not detected, suggesting a relatively high bar to escape. These data demonstrate the potential for antibody-based therapy and prevention of ZIKV. A single monoclonal antibody is therapeutic and has prophylactic activity against Zika virus in monkeys.